Investigation of melamine and cyanuric acid deposition in pig tissues using LC-MS/MS methods. (June 2015) - Tkachenko, Andriy; Clark, James; Knutson, Natalie; Wallace, Betzy; Bomba, Malgorzata; Yacopucci, Michele; Rhodes, Blaine; Nemser, Sarah M.; Guag, Jake; Reimschuessel, Renate
Highlights: A collaborative study evaluated four LC-MS/MS methods to detect and quantify melamine and cyanuric acid in pig tissues. Pigs treated with 200 mg/kg bw/day CYA for 7 days did not accumulate significant residues in muscle, liver or kidney. Pigs treated with 200 mg/kg bw/day MEL for 7 or 28 days resulted in significant MEL residues in muscles, liver and kidney. Pigs treated with both MEL + CYA at 1, 3 or 10 mg/kg bw/day for 7 days did not have residues above the level of concern. Pigs treated with a combination of MEL + CYA at 100 mg/kg bw/day had significant residues of both MEL and CYA. Abstract: Four LC-MS/MS methods were developed to quantify melamine (MEL) and cyanuric acid (CYA) in various pig tissues at or above the level of concern (2.5 mg/kg). Pigs treated with 200 mg/kg bw/day CYA daily for 7 days did not accumulate significant residue concentrations in muscle, liver or kidney. Pigs treated with 200 mg/kg bw MEL daily for 7 or 28 days had MEL residues in muscles (3–13 ppm), liver (2.8–14.1 ppm) and kidney (9.4–27.2 ppm). Treatment with MEL and CYA at 100 mg/kg bw of each triazine daily for 7 days resulted in MEL (26–59 ppm in muscle, 30–49 ppm in liver and 367–6300 ppm in kidney) and CYA (1.8–5.8 ppm in muscle, 2.6–6.5 ppm in liver and 303–7100 ppm in kidney). Treatment with MEL and CYA at 1, 3 or 10 mg/kg bw/day for 7 days did not result in residues greater than the level of concern in all tissues tested. Pigs dosed with 33 mg/kg bw/day of MEL + CYA for 7 days contained residues above the level of concern only in kidney. Deposition of MEL and CYA depends on the tissue type (muscles, liver and kidney), dosage and whether the triazines are given alone or in combination.